Randomized clinical trial comparing the efficacy and safety of treatment with the once‐weekly dipeptidyl peptidase‐4 (DPP‐4) inhibitor omarigliptin or the once‐daily DPP‐4 inhibitor sitagliptin in patients with type 2 diabetes inadequately controlled on metformin monotherapy. Issue 3 (17th January 2017) - Goldenberg, Ronald; Gantz, Ira; Andryuk, Paula J.; O'Neill, Edward A.; Kaufman, Keith D.; Lai, Eseng; Wang, Yin Na; Suryawanshi, Shailaja; Engel, Samuel S.
Abstract : Aim: To compare the efficacy and safety of the once‐weekly oral dipeptidyl peptidase‐4 (DPP‐4) inhibitor omarigliptin or once‐daily DPP‐4 inhibitor sitagliptin in patients with type 2 diabetes (T2DM) and inadequate glycaemic control on metformin. Materials and methods: Patients with T2DM with a glycated haemoglobin (HbA1c) concentration ≥6.5% to ≤9.0% while on a stable dose of metformin (≥1500 mg/d) were randomized in a double‐blind manner to receive omarigliptin 25 mg once weekly (n = 322) or sitagliptin 100 mg once daily (n = 320). The primary analysis assessed whether omarigliptin was non‐inferior to sitagliptin in reducing HbA1c at week 24, based on the criterion of having an upper bound of the 95% confidence interval (CI) about the difference less than the non‐inferiority bound of 0.3%. Results: The mean baseline HbA1c was 7.5% in both groups. After 24 weeks, the least squares (LS) mean change in HbA1c from baseline was −0.47% in the omarigliptin group and −0.43% in the sitagliptin group, with a between‐group difference of −0.03% (95% CI −0.15, 0.08). This result met the prespecified criterion for declaring non‐inferiority. The LS mean change from baseline in fasting plasma glucose and the percentage of patients with HbA1c <7.0% or <6.5% at week 24 were similar in the two treatment groups. There were no notable differences in adverse events and the incidence of symptomatic hypoglycaemia was low and similar in the groups. Conclusions: In patients with T2DM and inadequate glycaemic control on metformin, the addition of omarigliptin 25 mg once weekly or sitagliptin 100 mg once daily led to similar improvements in glycaemic control. Both agents were generally well tolerated with a low incidence of hypoglycaemia.